Integrating Religious and Secular Knowledge in “Salimna Official” with Educational Philosophy of Rasyid Ridha - Devi Lusiana Putri; Taufikin Taufikin; A'yuna Dzil Ma'unah; Adillah Shinta Al Azizati; Gulnaz Fatma (Universitas Muhammadiyah Mataram, 2025)
The rapid development of digital platforms has transformed the landscape of Islamic education; however, many pesantren still struggle to integrate digital dakwah with traditional learning systems. This research addresses this gap by examining how Salimna Official, a media platform of Pondok Pesantren Tahfidzul Qur’an An-Nasuchiyyah Kudus, integrates religious and secular knowledge within its digital content. Using a qualitative case study design, data were collected through semi-structured interviews, participatory observation, and documentation analysis, and were examined using thematic analysis to ensure methodological rigor and analytical clarity. The findings show three key patterns: (1) the integration of Islamic teachings with contemporary knowledge appears consistently in video content, infographics, and podcasts; (2) digital strategies such as content diversification, youth-centered engagement, and expert collaboration strengthen pedagogical relevance; and (3) these strategies are aligned with Rasyid Ridha’s educational philosophy, particularly his concept of harmonizing religious and worldly sciences. Scientifically, this study contributes to the discourse on digital Islamic pedagogy by offering an empirical model of integrated knowledge production in pesantren-based digital media. Practically, the study provides a replicable framework for pesantren seeking to strengthen digital dakwah, develop students’ multimedia skills, and enhance the relevance of Islamic education in the digital era.